Yemelianova O., Maga T. Political Phraseology and Features of its Translation in Modern English Journalistic Discourse - O. V. Yemelianova; T. M. Maga (Philological Treatises, 2020)
Nowadays, journalistic discourse takes one of the leading places in public life. One of its main aims is to influence the recipients and form their views and opinions with the help of pragmatic function of persuading. Here one can find a combination of concise logical thoughts that reflect the objective state of affairs and subjectivity, which reflects the author’s personal feelings and emotions in the subject matter under discussion. Phraseological units are an integral part of journalistic discourse, due to which there is a possibility to express the opinion or position of the author more clearly, or to form a positive or negative attitude to events, to reveal the emotional state of the speaker and to emphasize the attention of the recipients on the subject of the message. The richest modern phraseological layer concerns political life. These are the terminological names of the phenomena of political life, traditional phraseological units and proverbial phrases used by politicians in their speeches in order to give them a certain expression and increase the influence on the recipient, capture their attention. Political phraseology has not been studied extensively, therefore, it is necessary to identify its characteristic features and the specifics of its decoding in the language of translation.The translation of such linguistic units is quite complicated and delicate task, because a translator should convey the original author’s idea and preserve pragmatic effect of the text. Following methods of decoding are distinguished: phraseological equivalent, phraseological analogies, word-for-word translation and descriptive translation of phraseologisms. The correct perception and understanding of the phraseologisms also depend on the background knowledge and psychological sense of the recipients.